Penggunaan Pasir dan Serat Kayu Aren sebagai Media Tanam Terong dan Tomat dengan Sistem Hidroponik - Handiyan Kharisma Putra; Dwi Hardjoko; Hery Widijanto (Universitas Sebelas Maret, 2013)
Sands have large pores so can dry quickly by evaporation process. One attempt to do to improve the productivity of sands by increasing the water holding capability with addition of organic fibers. One of them is a waste of arenga wood fiber that has not been handled properly. The purpose of this research is to determine the composition of the sand media combinations of arenga wood fiber which most suitable for planting of eggplant and tomato. This research was carried out in June to September 2013 in the screenhouse of Badan Penyuluhan Pertanian Perikanan dan Kehutanan (BP3K) Cangkringan Sleman regency. This study used a Completely Randomized Design (CRD) using a single factor which 7 treatments tested on eggplant and tomato, each treatment was repeated 5 times. Experimental data were analyzed using analysis of variance and DMRT at 5% level. The results showed that the treatment of planting media only affects to eggplant leaf number and weight of fruit per plant on both commodities. The highest number of leaves produced by the use of charcoal husk is 25.2 strands. The highest eggplant fruit weight per plant produced by the use of the washed sand medium was 209.36 g and 352.72 g for tomato planted on doesn’t wash sand.